1998
DOI: 10.1136/gut.42.1.112
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of oestradiol on chemical hepatocarcinogenesis in rats

Abstract: Aims-To examine the eVects of oestradiol and testosterone on the early carcinogenic changes expressed in rat liver from the diethylnitrosamine (DEN), 2-acetylaminofluorene (AAF), partial hepatectomy (PH) model of hepatocarcinogenesis. Methods-Preneoplastic liver lesions were evaluated using immunohistochemical analysis of glutathione-S-transferase placental form (GST-P) expression; oestrogen and androgen receptor levels were measured by radioimmunoassay. Results-Oestradiol administration to non-castrated DEN-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(44 citation statements)
references
References 39 publications
2
42
0
Order By: Relevance
“…Although many controversies still exist with respect to the association between estrogen and HCC, evidence has been accumulating to show that estrogen may play a protective role against the HCC development in recent years [2,3]. However, currently, it remains unknown whether and how estrogen is linked to the distant metastases of HCC and, if so, which kind of mechanism is involved.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Although many controversies still exist with respect to the association between estrogen and HCC, evidence has been accumulating to show that estrogen may play a protective role against the HCC development in recent years [2,3]. However, currently, it remains unknown whether and how estrogen is linked to the distant metastases of HCC and, if so, which kind of mechanism is involved.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, accumulating evidence has shown that estrogen has certain protective role against the development of HCC. [2,3] However, data are still scarce about whether and how estrogen affects the distant metastasis of HCC.…”
Section: Introductionmentioning
confidence: 99%
“…In rodent HCC models, ovariectomy was reported able to increase the susceptibility of HCC in female mice [45,46]. Shimizu et al [55] also demonstrated a suppressive effect of estradiol administration in hepatocarcinogenesis using the DEN, 2-acetylaminofluorene, partial hepatectomy HCC model. In contrast, the synthetic estrogen was found to have the ability to promote hepatocarcinogenesis after initiation with DEN treatment [56,57,58], which in turn will not occur in the absence of the initiation event.…”
Section: Involvement Of the Estrogen Axis In Protecting Female Hcc: Ementioning
confidence: 92%
“…In addition, HCV-related cirrhotic women before menopause might also have the ability to protect against developing HCC via hepatic ER . Our previous reports also concluded that E2 suppresses hepatic chemical carcinogenesis (Shimizu et al, 1998) in animal models. These findings suggest that the putative cytoprotective and anticarcinogenic roles of E2 in the liver may contribute to the sexassociated differences observed in the development of chronic viral hepatitis.…”
Section: Introductionmentioning
confidence: 92%